A strategic approach to improve sustainability in transportation service procurement. (February 2015) - Jothi Basu, R.; Bai, Ruibin; Palaniappan, PL.K.
Highlights: This paper focuses on procurement of full truck load transportation service with the view of ensuring sustainability in business logistics. This paper studies the effect of combinatorial bidding on reducing empty haul in real world truck load procurement auction. Two heuristics methodologies have been proposed to solve the Carrier Assignment Problem (CAP) in full truck load contract auction. Findings reveal that the methodologies minimize cost as well as empty movement of trucks. Abstract: This paper focuses on the procurement of full truck-load transportation service with the view to ensuring sustainability in transport logistics. The carrier assignment problem (CAP) involved in truck load contract auction is studied using a complete enumeration method and heuristic approach. Performance of both methods is compared in terms of solution quality and computational time based on the results of sample problems considered. Also, the impact of combinatorial bidding on reducing empty haul in real world case is analyzed and environmental sustainability is achieved through reduction in carbon foot print.